Modification Pathways for Copoly(2‐oxazoline)s Enabling Their Application as Antireflective Coatings in Photolithography - Fimberger, Martin; Behrendt, Andreas; Jakopic, Georg; Stelzer, Franz; Kumbaraci, Volkan; Wiesbrock, Frank (Wiley, 2015)
Chromophore‐functionalized copoly(2‐oxazoline)s are successfully evaluated as bottom antireflective coatings (BARCs) in high‐resolution photolithography. With respect to UV light sources used in photolithographic production routines, anthracene is chosen as a chromophore. For application as polymer in BARCs, the copolymer poly(2‐ethyl‐2‐oxazolin)45‐stat‐poly(2‐dec‐9′‐enyl‐2‐oxazolin)20‐stat‐poly(2‐(3′‐(1″‐(anthracen‐9‐ylmethyl)‐1″,2″,3″‐triazol‐4‐yl)propyl)‐2‐oxazolin)35 can be synthesized by the Huisgen cycloaddition click reaction of the copolymer poly(2‐ethyl‐2‐oxazolin)45‐stat‐poly(2‐dec‐9′‐enyl‐2‐oxazolin)20‐stat‐poly(2‐pent‐4′‐inyl‐2‐oxazolin)35 and the corresponding azide‐functionalized anthracenes. These copolymers can be crosslinked by the thermally induced thiol‐ene reaction involving the unsaturated C=C bonds of the poly(2‐dec‐9′‐enyl‐2‐oxazoline) repetition units and a multifunctional thiol as crosslinker. Tests of this BARC in a clean room under production conditions reveal a significant decrease of the swing‐curve of a chemically amplified positive photoresist by more than 50%, hence significantly increasing the resolution of the photoresist. image
Keywords: Anthracenes; Refractometry; Optical Phenomena; Polymers; Chromatography, Gel; Printing; Models, Theoretical; Oxazoles